2015
DOI: 10.14411/fp.2015.023
|View full text |Cite
|
Sign up to set email alerts
|

Screening for anthelmintic resistance in equid strongyles (Nematoda) in Romania

Abstract: Resistance to anthelmintic medication of equid strongyles is a worldwide phenomenon and for this reason systematic investigations of resistant parasite populations are necessary. The purpose of the present study was to investigate the presence and distribution of equid strongyles resistant to the anthelmintics used in Romania, as well as the pre-treatment and post-treatment prevalence of species of strongylid nematodes. The Faecal Egg Count Reduction Test was performed between 2010 and 2013 on a total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
4
14
0
Order By: Relevance
“…Through larval culturing, this study revealed mixed strongyle populations, comprising a complex of cytostomin species, with the morphotype A as predominat, but also strongylin species, including S. vulgaris, S. edentatus, and S. equinus in working horses. These results are consistent also with previous studies carried out in Romania reporting a prevalence of 10.3% for S. vulgaris (Cernea et al, 2015). Different surveys showed that the S. vulgaris species is more commonly found in working horses, as it was in the present study, or in horses from farms where anthelmintic treatments are iregularly administered or with a lower intensity (Kyvsgaard et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…Through larval culturing, this study revealed mixed strongyle populations, comprising a complex of cytostomin species, with the morphotype A as predominat, but also strongylin species, including S. vulgaris, S. edentatus, and S. equinus in working horses. These results are consistent also with previous studies carried out in Romania reporting a prevalence of 10.3% for S. vulgaris (Cernea et al, 2015). Different surveys showed that the S. vulgaris species is more commonly found in working horses, as it was in the present study, or in horses from farms where anthelmintic treatments are iregularly administered or with a lower intensity (Kyvsgaard et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…The results show that bison strongyle populations are still very sensitive to benzimidazoles and tetrahydropyrimidines, totally diferent, compared to strongyle populations in horsers, which already developed a wide resistance against benzimidazoles, especially against ABZ (Cernea et al, 2015).…”
Section: Tabmentioning
confidence: 89%
“…From the EC 50 point of view, the maximum efficacy was recorded in MBZ and TBZ, the last being ABZ with a EC 50 of 0.326 mcg/ml. However, according to the standard interpretation of this test, in which the tested parasite population is considered to be resistant if the hatching percentage at the reference concentration (0.15 mcg/ml) is higher than 50% (Cernea et al, 2015;Coles et al, 1992), all tested benzimidazoles have been shown to present hatching percentages as low as 50%. From this point of view, the best efficacy was recorded with MBZ, followed by TBZ and ABZ.…”
Section: Tabmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrate content and soluble sugars are highly correlated to fruit abscission. BRs lead to a specific enhancement of leaf carbohydrate content [GOETZ et al, 2000, CERNEA, et al, 2015, BUTNARIU and GIUCHICI, 2011 . In this study, epibrassinolid treatments significantly increased the amount of carbohydrates in leaves while it reduced fruit and bud abscission.…”
Section: Fruit Characteristics; Inflorescence Bud and Fruit Abscissionmentioning
confidence: 99%